THE ROLE OF FINANCIAL LITERACY FOR SMEs OWNERS : STUDY ON RIBBON EMBROIDERY SMEs IN SEMARANG - Puspitasari, Diana; Wardhani, Masitha Fahmi; Herawati, Ratna (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2022)
The purpose of this study was to determine the understanding and role of business owners' financial literacy in terms of female gender in their business management, to explore any information that plays a role in increasing their business financial literacy intelligence, where Semarang City has ribbon embroidery SMEs whose ownership is dominated by the female gender. The number of ribbon embroidery SMEs in Semarang is not as many as Batik Semarangan SMEs but the results of the work and the results of the National Financial Literacy Survey (SNLIK) conducted by the Financial Services Authority (OJK) in 2019, the financial literacy of male owners is greater than that of women. The financial literacy of business actors (MSMEs), especially those of the female gender, is said to be still low below the male gender, this needed more attention so that these female business actors can improve their financial literacy intelligence, so they can be more effective in managing their businesses so that they continue to grow. survive and thrive. The research method used is qualitative with a narrative approach. to get a description of the data in the form of the level of understanding of the financial literacy of the owner as a business actor in managing his business and trying to capture interpretations from various perspectives of people who will be used as objects of research. The results of the study indicate that the indicators of education and length of business have a very significant role in business management. Based on the results of the research and discussion described above, it can be concluded that the level of education and the length of the business establishment have a major influence on the understanding of business owners. Because the higher one's education, the more open the mastery of one's knowledge in managing a good business from a financial perspective. While the length of business indicates that a person will be more skilled in managing his business both in terms of finance and production because they will be more honed in managing their business. The new variable used in this research is to include a cost-efficiency-based feminism variable which is a novelty as a development for this research.Keywords: Financial Literacy, Education, Income Level, Business Time, and Owner’s Age, a cost-efficiency-based feminism